Аналіз аспектів SMM просування бізнесу у соціальних медіа - Косенко, А. С. (ХНУРЕ, 2024)
Today's social networks are not just a place to get together with friends, but an effective way to run a business. Advertising in social media is a unique tool that helps you retain existing clients and gain new ones. Established companies that are focused on results and development are definitely not lacking in SMM. The work carried out an analysis of the theoretical aspects of SMM business promotion in social media, and an analysis of the ranking of social networks in the world and among Ukrainians. It was revealed that the average number of hours that workers are present at the social security level.
Keywords: SMM просування бізнесу; соціальні медіа